The existence of diversity in Sumbergondo Village Communities, Glenmore District, Banyuwangi Regency, 1949-2012 - Dimas Surya Dwi Cahyo; Sumarjono Sumarjono; Marjono Marjono (History Education, University of Jember, 2020)
There was expansion of Sumbergondo Village in 1949 due to a large population growth and a fairly large area covering the villages of Sumbergondo, Bumiharjo, Kaligondo, Tulungrejo now. With the expansion of the Village, Sumbergondo Village formed a unique cultural pattern and was harmoniously related between communities who had different beliefs, although separated in terms of territory and different in terms of belief, the people of Sumbergondo Village still uphold their ancestral beliefs from generation to generation to respect differences. and side by side are the characteristics of the Javanese tribe in general. Until now, the community still maintains the values ​​and norms contained therein, there are three religions whose people maintain each other and have high tolerance, namely Islam, Christianity, and Hinduism. The results of the study show the formation of diversity in Sumbergondo Village. can not be separated from the early entry of existing religions, among others, Hinduism, Islam and Christianity. interaction and mutual need for one another does not differentiate between one adherent and another. The suggestions in this research are expected to provide additional knowledge about the history of religious diversity and tolerance in Indonesia. Keyword: Diversity, Religion, Culture